Program Penggabungan Sekolah Dasar (SD) Dalam Meningkatkan Efektivitas dan Efisiensi Penyelenggaraan Pendidikan - Tita Setiawati (Universitas Mathla'ul Anwar Banten, 2018)
REGROUPING PROGRAM OF PRIMARY SCHOOL (SD) IN IMPROVING EFFECTIVENESS AND EFFICIENCY OF EDUCATION. The fact shows that the implementation of primary school level education must still receive attention, whether in the aspects of employment, finance, educational facilities and infrastructure which are still far from the desired expectations, the limited budget for education as well. The effort to improve the education budget appears to be in the current situation and condition, not yet possible to do. On the basis of that consideration, the policy of Primary School Regrouping is the most feasible effort to be done as a breakthrough step to realize efficiency and effectiveness in carrying out educational operational tasks. Judging from the public policy study the significance of the Elementary School regrouping program is to increase the success of effective and efficient primary school. While from the aspect of public interest, with the incorporation of Primary School can provide the best service to the public in the field of education. Further data obtained and the value of information that the policy of incorporation elementary school is appropriate to be implemented and has been able to create teaching and learning activities more effective and efficient. In addition, it has also been able to improve the work performance and motivation of principals and teachers in performing their duties, to improve the participation of the School Board significantly in assisting the smooth management of the school.